APLIKASI MANAJEMEN PENYETOKAN BARANG PADA TOKO HOAX COFFEE CAFE BERBASIS MOBILE - Solihin, Muhammad Arief; Dwinanda, Fevint Khrisma; Agusti, Iqbal (Universitas Muhammadiyah Palembang, 2020)
The increasing use of artificial phones on daily living and the increasing popularity of androids in society. This opens up opportunities in creating multipurpose applications using androids as their platforms, including the possibility of delivering goods. The hoax coffee cafe is a fast-moving cafe with a coffee beverage product as its principal one that daily daily practice hand-delivered goods. It caused the cafe owner some difficulties in making a tourniquet. The custom-stock application is designed to assist the cafe owner in making quick and precise alterations. Applying this application, it is expected to increase productivity and efficiency in presenting goods in this cafe's hoax coffee.Keywords: mobile,stock, Android